ANALISIS OPINI WAJAR TANPA PENGECUALIAN PADA LHP LKPD TERHADAP TINGKAT KORUPSI DI ACEH DENGAN KINERJA KEUANGAN DAERAH SEBAGAI VARIABEL INTERVENING - Maulana, Rizqie; Fuadi, Raida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
The purpose of this study is to investigate the relationship or influence of WTP opinion on the level of corruption with regional financial performance as an intervening variable in Aceh Province. The sample selection in this study used a non-probability sampling method with a purposive sampling approach. This study uses SEM-PLS analysis with WarpPLS version 7.0. The results obtained from data processing indicate that the exogenous variable, namely a direct relationship where the test results directly give the result that Unqualified Opinion on the 2017-2020 LKPD LHP has a significant effect on the Corruption Level in Aceh Province and an indirect relationship where Unqualified Opinion in the 2017-2020 LHP LKPD has no effect on the level of corruption with Regional Financial Performance as an Intervening Variable in Aceh Province.